2016
DOI: 10.2355/isijinternational.isijint-2016-361
|View full text |Cite
|
Sign up to set email alerts
|

Calculating the Macroscopic Dynamics of Gas/Metal/Slag Emulsion during Steelmaking

Abstract: The average residence time, metal circulation rates and percentage tap weights of metal suspended in the emulsion of a Basic Oxygen Furnace (BOF) are calculated under defined assumptions. Data has been taken from the IMPHOS (Improved Phosphorus Refining) project in which a 6 tonne BOF was simultaneously sampled at selected depths and at selected times under controlled operating conditions. 1) A discussion is given on the formation of the model and as to the diversion from previously reported findings from this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Previous work by the authors used a unique set of data from a pilot scale BOF and investigated the amount, residence time, and circulation rates of the emulsion metal, concluding from a simple carbon mass balance that approximately 60 pct of decarburization could be accounted for from metal packets in the emulsion zone. [62] This value is also supported by other literature sources with calculation methods including full-scale BOF sampling and fundamentally driven dynamic models. [63,64] Dynamic converter models are currently showing a strong potential to offer the level of understanding and parameter balancing required to fine-tune the gains in performance previously mentioned, which are required to ensure the viability of a steelmaking process long term.…”
Section: Behavior Of Metal Droplets In the Bofsupporting
confidence: 65%
“…Previous work by the authors used a unique set of data from a pilot scale BOF and investigated the amount, residence time, and circulation rates of the emulsion metal, concluding from a simple carbon mass balance that approximately 60 pct of decarburization could be accounted for from metal packets in the emulsion zone. [62] This value is also supported by other literature sources with calculation methods including full-scale BOF sampling and fundamentally driven dynamic models. [63,64] Dynamic converter models are currently showing a strong potential to offer the level of understanding and parameter balancing required to fine-tune the gains in performance previously mentioned, which are required to ensure the viability of a steelmaking process long term.…”
Section: Behavior Of Metal Droplets In the Bofsupporting
confidence: 65%
“…A mass balance approach to calculating these macro emulsion variables was taken by the current authors with extensive data published across multiple pilot scale trials. [52] The general trends were found to show metal volumes peaking between 4 and 6 min, residence times reached their highest of up to 120 s around midblow (8 min), and metal circulation rates steadily rose through the blow before an exponential increase at the end blow, which was rationalized due to foaming reduction and droplets moving through gas rather than a sustained emulsion. The macroscopic findings were compared against previous experimental trials [53] as well as an extensive study conducted by academics using first-principles reaction kinetics and modeled droplet generation understanding.…”
Section: Potential Contribution Of Droplets In the Bos Emulsionmentioning
confidence: 91%
“…Several authors indicated that the way the samples (in a blow, after blow stopping, height and time of sampling) are collected from the emulsion, can have a significant influence on droplet characteristics. [49,50] However, the sampling procedure was not mentioned in Jalkanen's study and thus the substantial reversion observed in the bulk metal due to the cause of slag/metal droplet reversion as predicted by the model, was not conclusively verified. This needs a further experimental study to investigate the reversion mechanism of Mn to establish the current hypothesis.…”
Section: Analysis Of Mn Reaction Kinetics In Emulsionmentioning
confidence: 88%